2015
DOI: 10.1007/s11097-015-9421-3
|View full text |Cite
|
Sign up to set email alerts
|

Situating the self: understanding the effects of deep brain stimulation

Abstract: The article proposes a theoretical model to account for changes in self due to Deep Brain Stimulation (DBS). First, we argue that most existing models postulate a very narrow conception of self, and thus fail to capture the full range of potentially relevant DBS-induced changes. Second, building on previous work by Shaun Gallagher, we propose a modified 'pattern-theory of self', which provides a richer picture of the possible consequences of DBS treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Analysing various accounts of this elusive yet familiar phenomenon, Dings and de Bruin (2016) claim that there is profound disagreement regarding a concept that adequately characterises the self in the context of the theoretical debate on the neuroethics of DBS. Furthermore, they argue that most approaches postulate relatively narrow concepts of the self, focusing on one or two of its aspects: the representational (Synofzik & Schlaepfer, 2008), cognitive (Witt et al, 2013), narrative (Schechtman, 2010), relational (Baylis, 2013), or enactive (de Haan et al, 2013) dimensions.…”
Section: Models Of the Self And Their Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysing various accounts of this elusive yet familiar phenomenon, Dings and de Bruin (2016) claim that there is profound disagreement regarding a concept that adequately characterises the self in the context of the theoretical debate on the neuroethics of DBS. Furthermore, they argue that most approaches postulate relatively narrow concepts of the self, focusing on one or two of its aspects: the representational (Synofzik & Schlaepfer, 2008), cognitive (Witt et al, 2013), narrative (Schechtman, 2010), relational (Baylis, 2013), or enactive (de Haan et al, 2013) dimensions.…”
Section: Models Of the Self And Their Problemsmentioning
confidence: 99%
“…The aim of this article, however, is not to resolve the complicated ontological issues discussed above, but rather to contribute to PTS by identifying and examining aspects of the self, which are not included in PTS's list, but surely deserve their own place on it. This is crucial for the success of the project of PTS as it aims to: "investigate the full range of potentially relevant DBS-induced changes" (Dings & de Bruin, 2016). This endeavour seems necessary because the list proposed in PTS lacks some important aspects of the self, as Dings and de Bruin themselves acknowledged.…”
Section: The Need To Include Moral Aspects Of the Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially closed-loop interaction-i.e. changing the parameters of a device based on the real-time sensing of neurophysiological data-may adversely affect the phenomenological experience of individuals, for example by altering the sense of agency, a subject's sense of authenticity and autonomy, or the self [50][51][52].…”
Section: Possible Neurophenomenological Effects Of Closed-loop Neurotmentioning
confidence: 99%
“…This strategy was proposed by Dings and de Bruin [133] in relation to their work on the therapeutic use of deep brain stimulation 20 in cases of obsessive-compulsive disorder (OCD). They mapped the DSM-5 definition of OCD onto PTS and found that all aspects of the symptomatology were mapped perfectly in PTS.…”
Section: Narrative As Reflecting the Self-pattern And As A Second-permentioning
confidence: 99%